The Meaning of Corporate Social Responsibility: The Vision of Four Nations - Freeman, Ina; Hasnaoui, Amir (2011)
Corporate Social Responsibility (CSR) has existed in name for over 70 years. It is practiced in many countries and it is studied in academia around the world. However, CSR is not a universally adopted concept as it is understood differentially despite increasing pressures for its incorporation into business practices. This lack of a clear definition is complicated by the use of ambiguous terms in the proffered definitions and disputes as to where corporate governance is best addressed by many of the national bodies legislating, mandating, or recommending CSR. This article explores the definitions of CSR as published on the Internet by governments in four countries (United Kingdom (UK), France, the United States, and Canada). We look for a consensus of understanding in an attempt to propose a more universal framework to enhance international adoption and practice of CSR using the triple bottom line. Our results concur with the findings of both national and international bodies and suggest that both within and among the countries in our study there exists no clear definition of the concept of CSR. While there are some similarities, there are substantial differences that must be addressed. We present a number of proposals for a more universal framework to define CSR.
Keywords: Canada; United States; France; United Kingdom; Definition; Corporate Social Responsibility